Relationships among water quality, food resources, fish diet and fish growth in polyculture ponds: a multivariate approach - Rahman, Mohammad Mustafizur; Nagelkerke, Leopold A.J.; Verdegem, Marc C.J.; Wahab, Md Abdul; Verreth, Johan A.J. (Elsevier B.V., 2008)
We examined the influence of addition of common carp (Cyprinus carpio) and artificial feed in rohu (Labeo rohita) ponds. We analyzed the relationships among four datasets on different components of the pond food web (water quality, food availability, natural food intake, and fish growth and production) with the aim to examine the effects of the addition of common carp and/or artificial feed on the different components of the pond food web, and to analyze the nature and strength of the interactions between these components. We used redundancy analysis (RDA) to investigate these effects and interactions. We found that the addition of common carp increased bio-available N and P in the water column. Artificial feed addition increased N and P only in the presence of common carp. N and P increases were more pronounced in the presence of 0.5 than in the presence of 1 common carp m−2. Plankton availability was strongly positively correlated with bio-available N and P. Phytoplankton availability correlated strongest with PO4–P, and zooplankton availability correlated strongest with PO4–P and DO. Natural food intake in rohu was positively correlated with plankton availability in the pond water and rohu growth was also positively correlated with natural food intake. Rohu preferred plankton over artificial feed, which acted as a fertilizer for rohu growth. Common carp preferred artificial feed over natural food and its growth was higher in the presence of artificial feed and negatively correlated with natural food availability.